Regulation of Soil Microbial Community Structure and Biomass to Mitigate Soil Greenhouse Gas Emission - Muhammad, Ihsan; Lv, Ju Zhi; Wang, Jun; Ahmad, Shakeel; Farooq, Saqib; Ali, Shamsher; Zhou, Xun Bo (Frontiers in Microbiology, 2022)
Sustainable reduction of fertilization with technology acquisition for improving soil quality and realizing green food production is a major strategic demand for global agricultural production. Introducing legume (LCCs) and/or non-legume cover crops (NLCCs) during the fallow period before planting main crops such as wheat and corn increases surface coverage, retains soil moisture content, and absorbs excess mineral nutrients, thus reducing pollution. In addition, the cover crops (CCs) supplements the soil nutrients upon decomposition and play a green manure effect. Compared to the traditional bare-land, the introduction of CCs systems has multiple ecological benefits, such as improving soil structure, promoting nutrient cycling, improving soil fertility and microbial activity, controlling soil erosion, and inhibiting weed growth, pests, and diseases. The residual decomposition process of cultivated crops after being pressed into the soil will directly change the soil carbon (C) and nitrogen (N) cycle and greenhouse gas emissions (GHGs), and thus affect the soil microbial activities. This key ecological process determines the realization of various ecological and environmental benefits of the cultivated system. Understanding the mechanism of these ecological environmental benefits provides a scientific basis for the restoration and promotion of cultivated crops in dry farming areas of the World. These findings provide an important contribution for the understanding of the mutual interrelationships and the research in this area, as well as increasing the use of CCs in the soil for better soil fertility, GHGs mitigation, and improving soil microbial community structure. This literature review studies the effects of crop biomass and quality on soil GHGs emissions, microbial biomass, and community structure of the crop cultivation system, aiming to clarify crop cultivation in theory.